Whole genome sequencing of extended-spectrum β-lactamase producing Klebsiella pneumoniae isolated from a patient in Lebanon - Tokajian, Sima; Eisen, Jonathan A.; Jospin, Guillaume; Farra, Anna; Coil, David A. (Frontiers in Cellular and Infection Microbiology, 2015)
Objective: The emergence of extended-spectrum β-lactamase (ESBL)-producing bacteria is now a critical concern. The ESBL-producing Klebsiella pneumoniae constitutes one of the most common multidrug-resistant (MDR) groups of gram-negative bacteria involved in nosocomial infections worldwide. In this study we report on the molecular characterization through whole genome sequencing of an ESBL-producing K. pneumoniae strain, LAU-KP1, isolated from a stool sample from a patient admitted for a gastrointestinal procedure/surgery at the Lebanese Amrican University Medical Center-Rizk Hospital (LAUMCRH) in Lebanon. Methods: Illumina paired-end libraries were prepared and sequenced, which resulted in 4,220,969 high-quality reads. All sequence processing and assembly were performed using the A5 assembly pipeline. Results: The initial assembly produced 86 contigs, for which no scaffolding was obtained. The final collection of contigs was submitted to GenBank. The final draft genome sequence consists of a combined 5,632,663 bases with 57% G+C content. Automated annotation was performed using the RAST annotation server. Sequencing analysis revealed that the isolate harbored different β-lactamase genes, including blaoxa−1, blaCTX−M−15, blaSHV−11, and blaTEM−1b. The isolate was also characterized by the concomitant presence of other resistance determinants most notably acc(6′)-lb-cr and qnrb1. The entire plasmid content was also investigated and revealed homology with four major plasmids pKPN-IT, pBS512_2, pRSF1010_SL1344, and pKPN3. Conclusions: The potential role of K. pneumonia as a reservoir for ESBL genes and other resistance determinants is along with the presence of key factors that favor the spread of antimicrobial resistance a clear cause of concern and the problem that Carbapenem-non-susceptible ESBL isolates are posing in hospitals should be reconsidered through systematic exploration and molecular characterization.